The Use of VoiceTube To Train Students With Speaking Anxiety in Inclusive Classroom - Nurul Hidayah Lubis; Maslathif Dwi Purnomo (Journal of Educational Sciences, 2026)
Speaking anxiety remains one of the most significant barriers affecting students’ oral participation and communication performance in English as a Foreign Language (EFL) classrooms, particularly in inclusive educational settings. This study investigates the use of VoiceTube as a technology-assisted learning platform to support students experiencing speaking anxiety in an inclusive English classroom. Employing a qualitative Classroom Action Research (CAR) design, the study was conducted over two cycles involving planning, action, observation, and reflection stages. Data were collected through classroom observations and semi-structured interviews with teachers and analyzed using thematic analysis. The research participants consisted of 3 eleventh-grade students in an inclusive class in Medan, including several students who showed speaking anxiety, such as reluctance to participate, avoiding eye contact, and hesitation during speaking activities. Following the implementation of VoiceTube-based learning activities, students showed greater engagement, increased participation, and improved confidence in speaking tasks. Furthermore, consistent teacher support through encouragement and positive reinforcement contributed significantly to reducing learners’ fear of negative evaluation and fostering active classroom participation. These findings suggest that VoiceTube can serve as a valuable instructional tool for promoting speaking confidence and participation among students with speaking anxiety in inclusive EFL classrooms.